Optimalisiasi Wakaf Produktif dalam Mendukung Upaya Pencapaian SDGs Melalui Pemberdayaan Peternakan - Abiba, Riska Widya; Suprayitno, Eko (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
This study aims to analyze the role of productive waqf through the livestock empowerment program to achieve Sustainable Development Goals (SDGs) in Indonesia which focuses on the first goal, namely no poverty and goal eight, namely decent work and economic growth. The research method used is qualitative research with a literature study approach. Data analysis technique using data reduction, data presentation, and data organization. The results of this study indicate that the potential for productive waqf in Indonesia is enormous, but the utilization of waqf assets still needs to be improved. So, the innovations emerged related to productive waqf through livestock waqf, where the waqf can play a role in developing and solving Indonesia's economic problems. Livestock waqf also contributes to achieving the Sustainable Development Goals (SDGs) by supporting the SDGs goal of a society without poverty, providing decent work, and increasing economic growth.